ANALISIS PENINGKATAN MIGRASI PADA MASYARAKAT DUSUN KADUNDUNG DESA PENGKENDEKAN KECAMATAN SABBANG KABUPATEN LUWU UTARA - Rusdi Rusdi; Feri Padli; Pujawati Pujawati (Universitas Khairun, 2022)
Research objectives to find out 1). Factors increasing migration In the Kadundung Hamlet Community, Pengkendekan Village, Sabbang District, North Luwu Regency, 2). Knowing the consequences increased migration in the Kadundung Hamlet Community, Pengkendekan Village, Sabbang District, North Luwu Regency. Type of research used n is descriptive qualitative. Data collection techniques are observation, interviews and documentation. Data analysis carried out is preparing data, reflecting on data, coding data, sharing coding results, interpreting and interpreting data.The research results show 1). There are three factors for increased migration namely: first, the driving factor which consists of a lack of jobs in origin, non-strategic location, natural disasters. Second, factor The bottlenecks consist of the long distance to the destination area and the high transportation costs expensive. Third, the pull factor consists of the expectation of more economic life well, geographical conditions in a strategic destination area and invitations from friends or brother. 2). There are two impacts of increased migration: first, impact positive is the reduction of unemployment in the village and can increase welfare of families in the village with remittances from relatives work in the city. Second, the negative impact is the lack of workers and villages become undeveloped